Methodological Developments and Innovations of the National Crime Victimization Survey, 1972–2023 - Cantor, David (Journal of contemporary criminal justice, 2025)
Over its 50 years of existence, the National Crime Victimization Survey (NCVS) has changed to address the informational needs of its users, as well as adapt to an evolving survey climate. Perhaps more than any other victim survey in the world, data quality has been an emphasis. In this article, the evolution of the methodology of the survey is described up to the point of the 2024 redesign. The first section provides an abbreviated description of the innovations and methods instituted up through the redesign in 1992. This section highlights key milestones and refers the reader to more detailed descriptions of the origins of the NCVS and the 1992 redesign. The second section provides more detail on methodological issues and changes since the 1992 redesign. This article closes with the challenges the survey faces moving forward into the mid-21st century.